The Effect Of Giving Maggot Meal (Black Soldier Fly) In The Ration On The Percentage Of Boneless Meat In Merawang Chickens - Muhammad Sahlan Adi Saputra; Anggraeni; Ristika Handarini (Universitas Djuanda, 2025)
Merawang chicken is a dual–purpose type of chicken whose egg and meat production is relatively high. The use of fish meal in chicken feed plays a role in the formation of chicken meat, but the high price and availability of feed are obstacles in rearing. The use of Black Soldier Fly (BSF) maggots can be an alternative feed to replace fish meal because it has a protein content of around 60%. The aim of this research was to test the effect of giving maggot meal as a substitute for fish meal in the ration on the percentage of boneless meat in merawang chickens. This research was conduced at Papidoka Farm (Caringin, Bogor) from October 2023 to November 2023. The study used 60 merawang chickens on 9 weekold with an average body weight ranging from 721.8 ± 68.6 g/bird. The research design used was a Completely Randomized Design (CRD) with 5 treatments and 4 replications, and the test results were analyzed using IBM SPSS for ANOVA and Duncan's advanced test. The treatment given in the ration is P0 = 0% maggot meal + 10% fish meal, P1 = 2.5% maggot meal + 7.5% fish meal, P2 = 5% maggot meal + 5% fish meal, P3 = 7, 5% maggot meal + 2.5% fish meal, P4 = 10% maggot meal + 0% fish meal. The variables observed were the percentage of meat, the percentage of boneless meat, the percentage of bone, and the percentage of skin on the breast and thighs of the merawang chicken. The results of the analysis of variance showed that giving maggot meal as a substitute for fish meal at a level of 0 – 10% in the ration of merawang chickens had a significant effect (P<0.05) on breast percentage, boneless meat percentage, breastbone percentage, breast skin percentage, thigh percentage, thighless meat percentage, thighbone percentage, thigh skin percentage and meat bone ratio (MBR) of chicken breasts and thighs. The conclusion of this research is that giving maggot meal as a substitute for fish meal at a level of 5% maggot meal and 5% fish meal can increase the percentage of boneless breast and thigh meat.